Gender dan Legitimasi Penentuan Awal Bulan Kamariah - Machzumy, Machzumy; Syarif, Muh Rasywan (ELFALAKY: Jurnal Ilmu Falak, 2020)
Rukyatul hilal activity is an annual agenda of the Ministry of Religion of the Republic of Indonesia to determine the entry of the early lunation month. As for the focus of the hilal rukyatul activity is the emergence of the new moon itself. So far, the determination of the beginning of the month is only done by male seaman, whereas women celestial experts also have the same opportunities and rights. But so far, the authors have not found any reports of hilal rukyat from women. This research uses library research method with a qualitative approach. The results of this study indicate that in the initial determination of the lunar month, female astronomers do not yet have the same rights and position as men.Keyword: Determination of Kamariah, Gender